A model for the performance assessment of hybrid coolers by means of transient numerical simulation. (1st November 2016) - D'Antoni, M.; Romeli, D.; Fedrizzi, R.
Highlights: Numerical modelling of heat and mass transfer phenomena in an air-based heat rejection component. Definition of a modular coil geometry for staggered finned-tube heat exchangers. Calculation of wettability factors for tube and fins. Definition of control strategies for fan speed and spray water cycles. Abstract: This paper presents the development of a numerical model of a hybrid cooler for transient simulation purposes as a component of a thermal energy system. The model uses a modular definition of the control volume, and is suitable for modelling any staggered coil geometry. The set of parameters required for modelling the hybrid cooler is typical of the so-called design models. A rigorous analysis of sensible and latent heat fluxes due to spray water evaporation is included. Further, the model can be exploited for the development of user-defined control strategies of fans and water spray systems. The model is validated using monitored data from a pilot system installation in which a commercial hybrid cooler is operated under typical summer south European working conditions.